PSYCHOLOGICAL ENGINEERING AND ITS RELATION TO PSYCHOLOGICAL ENDURANCE AND OFFENSIVE TACTICAL INTELLIGENCE FOR THE PLAYERS OF THE SWORD FIGHTING (SABRE) (Proximus Journal of Sports Science and Physical Education, 2025)
The psychological aspects and tactical intelligence offencing players. The research hypothesis was based on the existence of a significant correlation between psychological engineering, psychological endurance, and offensive tactical intelligence among the research sample. The problem of the research was to answer the following question: What level do fencing players possess in psychological engineering, psychological endurance, and offensive tactical intelligence? And what is the relationship between psychological engineering and psychological endurance and offensive tactical intelligence among the players? The research community consisted of the players of the sub-union of Kirkuk clubs, totaling (36) players, and the research sample included (36) players, representing 100% of the original community, along with (6) players for the exploratory trial . Questionnaires were distributed to the research sample, and results were extracted using statistical methods. Theresearcher reached a number of findings, including that the players distinguished themselves with a high level of psychological engineering, psychological endurance, and offensive tactical intelligence, and there was a significant correlation among them. The researcher recommended conducting studies similar to the current study and paying attention to the psychological aspect alongside the physical and skill-related aspects due to their significant role in achieving success